KARAKTERISTIK HABITAT DAN KUALITAS AIR TERHADAP KEBERADAAN JENTIK Aedes spp DI KELURAHAN SUKARAMI PALEMBANG - Indah Margarethy; Nungki Hapsari Suryaningtyas; Desy Asyati (SPIRAKEL, 2017)
Sukarami regency is one of the areas with the highest dengue cases in Palembang City. The presence of larvae will affect the mosquito population of dengue vectors. The spot has several characteristic differences that will affect the Aedes spp mosquito. to meet the eggs This study aims to determine the relationship between larvae habitat with habitat characteristics and air quality. The sample of this research is 100 homes inhabited as residence in Sukarami Village. Collection of Aedes spp larvae. with single larvae method. Aedes spp larvae habitat habitat data collection through the form. Measurement of water quality in Aedes spp larvae habitat. carried out to obtain water temperature, pH and salinity. The resulting data is then processed and categorized based on each variable. The analysis using bivariate using chi-square test to know the relationship between habitat characteristics and water quality with larvae area. The results showed significant differences between container type, container wall surface, container location, cover condition and water pH with Aedes spp larvae seeds (p <0.05). DHF surveillance activities through cadre empowerment for widening and Aedes spp eradication larvae should be undertaken as an effort to restore the chain of Aedes spp mosquitoes and propagation.